Kinematic analysis of Kai Zou's stoop in shoot and 1/1 turn through handstand in undergrgrip on horizontal bar - Liu, L.; Zhou, J.; Cheng, L.; Liu, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The stoop in shoot and 1/1 turn through handstand.in undergrip performed by Kai Zou, who was the champion of the World Championship in London(2009)and Tokyo(2011), and was 3-D recorded and analyzed. The athlete was analysed with kinematic technical model based on rules of gymnastics and theory of sports biomechanics,. The kinematic characteristics of this high skilled movement was analyzed to provide useful information for the technical training of coaches and athletes, and enriched theories of horizontal bar.